A prospective pilot study of the effect of acupuncture on insulin sensitivity in women with polycystic ovary syndrome and insulin resistance. Issue 5 (October 2020) - Li, Juan; Wu, Wanting; Stener-Victorin, Elisabet; Ng, Ernest Hung Yu; Li, Raymond Hang Wun; Li, Meifang; Liu, Hua; Lai, Maohua; Meng, Yanbing; Zheng, Yanhua; Xia, Yang; Ma, Hongxia
Objective: To test the hypothesis that acupuncture improves insulin sensitivity in women with polycystic ovary syndrome (PCOS) and insulin resistance (IR). Design: Prospective pilot study. Setting: Guangzhou, China, 2014–2016. Participants: Eighty women with PCOS aged 18–40 years with body mass index (BMI) above 18.5 kg/m 2 and with homeostatic model assessment for insulin resistance (HOMA-IR) index ⩾2.14. Interventions: Subjects received acupuncture with combined manual and low-frequency electrical stimulation of the needles three times per week for 6 months. Primary and secondary outcome measures: The primary outcome was the change in HOMA-IR after 6 months of acupuncture relative to baseline. Secondary outcomes included changes after 6 months of acupuncture and at 3 months of follow-up (both relative to baseline) in oral glucose tolerance test (OGTT) parameters (glucose and insulin levels), anthropometric measurements, and circulating metabolic and endocrine variables. Results: HOMA-IR and fasting plasma glucose and insulin levels were significantly decreased after 6 months of acupuncture, and both HOMA-IR and fasting insulin remained significantly decreased at 3 months of follow-up. In a subgroup analysis of normal-weight and overweight/obese women, HOMA-IR was reduced after 6 months of acupuncture in both subgroups, but there was no significant difference between the two groups. Conclusions: Acupuncture treatment in Chinese women with PCOS and IR was associated with an encouraging improvement in insulin sensitivity. Further randomized controlled studies are required to confirm the efficacy of acupuncture for this indication.